2023
DOI: 10.1142/s0219622023300033
|View full text |Cite
|
Sign up to set email alerts
|

Imputed Expert Decision Recommendation System for QFD-based Omnichannel Strategy Selection for Financial Services

Abstract: In this study, a novel hybrid fuzzy decision-making model is constructed for the effective omnichannel strategy selection of financial services. The first phase of this model is related to inputting missing expert decisions for the quality function deployment (QFD) stages and omnichannel service strategies. The QFD stages of financial services are then weighted by bipolar [Formula: see text]-rung orthopair fuzzy ([Formula: see text]-ROF) multi-stepwise weight assessment ratio analysis ([Formula: see text]-SWAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Newer methodologies have also been used in QFD in recent case studies, including hesitant fuzzy linguistics [36,73,74], fuzzy DEMATEL [39,75], grey relational analysis (GRA) [37,42,46,47,76], interval-valued fuzzy numbers (IVFN) [65,77], fuzzy Delphi method (FDM) [37,39,40,46,47,49,75], complex proportion assessment method (COPRAS) [78], ordinal priority approach-combinative distance-based assessment (OPA-CODAS) [79], social network analysis (SNA) [80], multi-stepwise weight assessment ratio analysis (M-SWARA) [81], entropy weight method (EWM) [38], double hierarchy hesitant linguistic term sets (DHHLTSs) [36], organísation, rangement et synthèse de données relarionnelles (ORESTE) [36], best-worst method-based [39,82], combined compromise solution (Co-CoSo) [43,70], Dempster-Shafer Theory (DST) [83], fuzzy cognitive maps (FCM) [84], proportional hesitant fuzzy linguistic term sets (PHFLTSs) [85], cumulative prospect theory (CPT) [85], fuzzy measuring attractiveness by a categorically based evaluation technique (FMACBETH) [40], and fuzzy full consistency method (FUCOM) [35,86].…”
Section: Other Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Newer methodologies have also been used in QFD in recent case studies, including hesitant fuzzy linguistics [36,73,74], fuzzy DEMATEL [39,75], grey relational analysis (GRA) [37,42,46,47,76], interval-valued fuzzy numbers (IVFN) [65,77], fuzzy Delphi method (FDM) [37,39,40,46,47,49,75], complex proportion assessment method (COPRAS) [78], ordinal priority approach-combinative distance-based assessment (OPA-CODAS) [79], social network analysis (SNA) [80], multi-stepwise weight assessment ratio analysis (M-SWARA) [81], entropy weight method (EWM) [38], double hierarchy hesitant linguistic term sets (DHHLTSs) [36], organísation, rangement et synthèse de données relarionnelles (ORESTE) [36], best-worst method-based [39,82], combined compromise solution (Co-CoSo) [43,70], Dempster-Shafer Theory (DST) [83], fuzzy cognitive maps (FCM) [84], proportional hesitant fuzzy linguistic term sets (PHFLTSs) [85], cumulative prospect theory (CPT) [85], fuzzy measuring attractiveness by a categorically based evaluation technique (FMACBETH) [40], and fuzzy full consistency method (FUCOM) [35,86].…”
Section: Other Methodologiesmentioning
confidence: 99%
“…In the first four months of 2023, 13 studies were identified to achieve supply chain targets [83,87,88] and improvement products [57,89] in post COVID-19 scenarios [87] and also in the energy sector, where an interesting approach was used to address sustainable targets based on a life cycle assessment (LCA) [62] and the creation of roadmaps [82]. The methodologies in HoQ structure are mainly AHP [57], fuzzy AHP [62], and hybrid fuzzy models such as [81,83], PROMETHEE II [89] and TOPSIS [63]. These case studies were applied in the supply chain, sustainability, and design and product development.…”
Section: Publications Per Yearmentioning
confidence: 99%
See 1 more Smart Citation
“…First, weights can be easily calculated with the SWARA method. In addition, the SWARA method can perform consistency analysis of comparisons (Kou et al, 2023a). In this way, it can be checked whether the data received from users is consistent.…”
Section: M-swara With Qpfrsmentioning
confidence: 99%
“…An accurate pricing model makes it possible to offer appropriate pricing to customers' demands and to gain a competitive advantage (Njegomir and Demko-Rihter 2023). Insurtech companies must gain a competitive advantage in the industry by developing new products and services tailored to their customers' needs (Kou et al 2023). New product development is a vital factor in increasing the growth potential of insurtech companies (Tladinyane et al 2022).…”
Section: Introductionmentioning
confidence: 99%